Combined Machining Principle of Milling and Form Grinding of Special Screw Rod - Zhang Huifang; Yang Guijuan (Jixie chuandong)
Aiming at the problem of poor quality of the special screw rod surface,a combined machining method of milling and form grinding based on non-instantaneous pole envelop method is proposed. Firstly,the kinematic relationship between the disk milling cutter and special screw rod is established on the basis of non-instantaneous pole envelop method. Then the cutter location points are calculated for milling the special screw rod. Secondly,according to the mesh principle of form grinding and the space meshing relationship between the forming grinding wheel and special screw rod,the contact line between the form grinding wheel and special screw rod is solved,the calculation method of the form grinding wheel profile is derived. Lastly,through the simulation manufacturing,the correctness of the proposed method for calculating the cutter location points and grinding wheel profile based on non-instantaneous pole envelope method is verified.